Performance of Forward Osmosis (FO) Membrane Fabricated from Different Molecular Weight of Polyvinylpyrrolidone (PVP) Additive - Nur Aisyah, Shafie; Mazrul Nizam, Abu Seman; Syed Mohd Saufi, Tuan Chik; Abdul Wahab, Mohammad (AIDIC Servizi, 2023)
Despite of the emergence of revolutionary Forward Osmosis (FO) technology, the membrane is hindered by the severe effect of internal concentration polarization (ICP) which generated in membrane substrate layer. In current study, polyethersulfone (PES) membranes substrate layer were fabricated via phase inversion using three different polyvinylpyrrolidone (PVP; molecular weight of 10 kDa, 40 kDa and 360 kDa) which act as a pore former agent. Using 2 wt% of aqueous m-phenylenediamine (MPD) and 0.15 wt% of trimesoyl chloride (TMC) in hexane, the active polyamide layer was formed on the top surface of PES substrate via interfacial polymerization to produce thin film composite (TFC) FO membrane. The performance of TFC FO membranes were evaluated and three intrinsic parameters; A, B and S were determined by mathematical model. The results attained were compared to find the optimized PVP molecular weight for FO membranes with desired performance. It was observed that FO membrane prepared with molecular weight PVP of 40 kDa exhibited excellent performance with low ICP, thus reduce the replacement of draw solute in FO application.